Implementation of Extracurricular Drumband in Training Students' Discipline at State Elementary School - Sholiha, Mar'atus (BASICA Journal of Arts and Science in Primary Education, 2024)
Background: students who take part in extracurricular drumband can train students' discipline. The aim of this research is to analyze how drumband extracurriculars are implemented in training students' discipline. This research method uses descriptive qualitative research. Data collection instruments in this research used interviews, observation and documentation. The data validity technique used includes data source triangulation. The results of the research showed that the 38 students who took part in drumband extracurriculars experienced an increase in discipline. This is proven by the fact that 34 students experienced an increase in discipline, while 4 students still arrived late. In general, the implementation of the drumband extracurricular in training discipline at SD Negeri 158 Mojosarirejo Gresik was successful because most of the students showed good discipline, but 4 students still arrived late. So, overall the discipline category is considered good.